Instruments and risks in islamic financial institutions / Rashidah Abdul Rahman, Fauziah Hanim Tafri and Yaseen Al Janadi. - Abdul Rahman, Rashidah; Tafri, Fauziah Hanim; Al Janadi, Yaseen (Universiti Teknologi MARA Cawangan Selangor, 2010)
The nature of specific risks facing Islamic Financial Institutions (IFIs) together with the virtually unlimited number of ways available to them to provide funds through the use of combinations of the permissible Islamic modes of financing, profit and loss sharing (PLS) modes of financing and non-PLS, raises a host of issues among others in risk management. This paper presents and explains the different types of risks arising from Musharakah, Mudharabah, Murabahah, Salam, Istisna and Ijarah Islamic products. Further, it highlights how financial institutions that provide such Islamic financial contracts are exposed to several corresponding underlying risks, as well as how these risks are managed.